The Analysis of Water Quality Compliance of Jompo River Irrigation in Jember Regency - Sri Wahyuningsih; Elida Novita; Idah Andriyani; Indarto Indarto (International Journal on Food, Agriculture and Natural Resources, 2021)
Jompo river is one of many tributaries in Jember regency has become one of water sources for residents nearby to meet their daily needs. People activities may lead to the emergence of pollution in Jompo river in long term. The measurement needs to determine water quality of the river. The research site ranged from Patrang to Kaliwates district with six nodes and covered a distance of 625 m. Based on the data analysis, average value of water quality in the river was characterized by 67 mg/l TSS (Total Suspended Solids), 72 mg/l TDS, pH at 6.73, 8.34 mg/l DO, 1.20 mg/l BOD, and EC at 145 µmhos/cm. Based on Government Regulation No. 82 of 2001 and Electricity value, the water quality of Jompo river was included in Grade II criteria. Jompo River was appropriate to irrigation water.